Raising Honest Citizens: A Cross-Cultural Study of Moral Education in Primary Schools - Hidayat, Muhamad Taufik; Khoirurrosyid, Muhammad; Kurniawan, Tegar Robby; Hening, Putri Pramesti; Ulya, Ghonni Afifatul; Sain, Zohaib Hassan (Jurnal Prima Edukasia, 2023)
This study explores the comparative implementation of honesty character education in elementary schools across four countries: Indonesia, New Zealand, Finland, and Japan. Honesty, as a core moral value, is widely acknowledged, yet its pedagogical realization varies across educational systems. Using a qualitative comparative literature review approach, this research examines how honesty is defined, integratd into curricula, delivered through pedagogical strategies, and supported by sociocultural contexts. The analysis reveals that Finland and Japan demonstrate systemic coherence in cultivating honesty-Finland through a trust-based and student-centered approach, and Japan through formal moral education (doutoku) and cultural internalization of makoto. New Zealand promotes honesty through democratic classroom practices and formative assessment. Indonesia, while normatively embracing honesty through curriculum policy, often lacks consistency in classroom implementation and parental collaboration. Findings also highlight the critical role of teacher modeling, student agency, and family-school alignment in reinforcing honest behavior. The study recommends that Indonesia enhance its honesty education through explicit curricular design, pedagogical training for value-based teaching, and increased family engagement. By adopting adaptable practices from global exemplars, Indonesia can strengthen its efforts in developing integrity-driven students equipped for ethical citizenship. This study contributes to the discourse on character education by offering practical insights grounded in cross-cultural comparison.